Identification of iron and zinc responsive genes in pearl millet using genome-wide RNA-sequencing approach - Goud, Chengeshpur Anjali; Satturu, Vanisri; Malipatil, Renuka; Viswanath, Aswini; Semalaiyappan, Janani; Kudapa, Himabindu; Rathod, Santosha; Rathore, Abhishek; Govindaraj, Mahalingam; Thirunavukkarasu, Nepolean (Frontiers in Nutrition, 2022)
Pearl millet (Pennisetum glaucum L.), an important source of iron and zinc for millions of families in dryland tropics, helps in eradicating micronutrient malnutrition. Being rich in Fe and Zn, identification of the key genes operating in mineral pathways is an important step to accelerate the development of biofortified cultivars. In a first of-its-kind experiment, leaf and root samples of a pearl millet inbred ICMB 1505 was exposed to combinations of Fe and Zn stress conditions using hydroponics method and a whole-genome transcriptome assay was carried out to characterize the differentially expressed genes (DEGs) and pathways. A total of 37,093 DEGs under different combinations of stress conditions was identified, of which, 7,023 and 9,996 DEGs were reported in the leaf and root stress treatments, respectively. Among the 10,194 unique DEGs, 8,605 were annotated to cellular, biological, molecular functions and 458 DEGs were assigned to 39 pathways. The results revealed the expression of major genes related to mugineic acid pathway, phytohormones, chlorophyll biosynthesis, photosynthesis, and carbohydrate metabolism during Fe and Zn stress. The cross-talks between the Fe and Zn provided information on their dual and opposite regulation of key uptake and transporter genes under Fe and Zn deficiency. SNP haplotypes in rice, maize, sorghum and foxtail millet as well as in Arabidopsis using pearl millet Fe and Zn responsive-genes could be used for designing the markers in staple crops. Our results will assist in developing Fe and Zn-efficient pearl millet varieties in biofortification breeding programs and precision delivery mechanisms to ameliorate malnutrition in South Asia and Sub-Saharan Africa.